2016
DOI: 10.1007/s00284-016-1009-9
|View full text |Cite
|
Sign up to set email alerts
|

Induction of nodD Gene in a Betarhizobium Isolate, Cupriavidus sp. of Mimosa pudica, by Root Nodule Phenolic Acids

Abstract: A range of phenolic acids, viz., p-coumaric acid, 4-hydroxybenzaldehyde, 4-hydroxybenzoic acid, protocatechuic acid, caffeic acid, ferulic acid, and cinnamic acid have been isolated and identified by LC-MS analysis in the roots and root nodules of Mimosa pudica. The effects of identified phenolic acids on the regulation of nodulation (nod) genes have been evaluated in a betarhizobium isolate of M. pudica root nodule. Protocatechuic acid and p-hydroxybenzoic acid were most effective in inducing nod gene, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The phenolic acids such as PA, VA, CaA, 4CoA and 4HBA identi ed in this study could have contributed to enhanced biological nitrogen xation (BNF) by promoting rhizobial growth and nodule development (Klein et Mandal et al 2016). Several bacterial strains were identi ed in the V. unguiculata nodules and these included Bacillus, Paenibacillus, Rhizobium, Bradyrhizobium and Delftia strains (Table 1) (Makaure et al 2022).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The phenolic acids such as PA, VA, CaA, 4CoA and 4HBA identi ed in this study could have contributed to enhanced biological nitrogen xation (BNF) by promoting rhizobial growth and nodule development (Klein et Mandal et al 2016). Several bacterial strains were identi ed in the V. unguiculata nodules and these included Bacillus, Paenibacillus, Rhizobium, Bradyrhizobium and Delftia strains (Table 1) (Makaure et al 2022).…”
Section: Discussionmentioning
confidence: 86%
“…The phenolic acids PA, VA, CaA, 4CoA and 4HBA exuded by V. unguiculata could have helped in nod gene expression regulation of the Rhizobium and they could have modi ed the legume-Rhizobium symbiosis (Schultze and Kondorosi 1998, Seneviratne and Jayasinghearachchi 2003). In earlier studies, PA and p-HBA acids were shown to effectively induce nod gene in root nodules of Mimosa pudica (Mandal et al 2016). It is evidenced that CaA enhanced the enzymatic levels in N 2 xation and it increased the levels of carbohydrates and proteins in legume nodules (Dhir et al 1992).…”
Section: Discussionmentioning
confidence: 94%